Development and initial validation of the Cardiovascular Disease Acceptance and Action Questionnaire (CVD-AAQ) in an Italian sample of cardiac patients - Spatola, Chiara A. M.; Cappella, Emanuele A. M.; Goodwin, Christina L.; Baruffi, Matteo; Malfatto, Gabriella; Facchini, Mario; Castelnuovo, Gianluca; Manzoni, Gian Mauro; Molinari, Enrico (Frontiers in Psychology, 2014)
Psychological inflexibility refers to the attempt to decrease internal distress even when doing so is inconsistent with life values, and has been identified as a potential barrier to making and maintaining health behavior changes that are consistent with a heart-healthy lifestyle. Disease- and behavior-specific measures of psychological inflexibility have been developed and utilized in treatment research. However, no specific measure has been created for patients with heart disease. Thus, the CardioVascular Disease Acceptance and Action Questionnaire was developed. The present study is aimed to evaluate the psychometric properties of the CardioVascular Disease Acceptance and Action Questionnaire and to explore its association with measures of psychological adjustment and cardiovascular risk factors in an Italian sample of 275 cardiac patients. Exploratory factor analysis showed a structural one-factor solution with satisfactory internal consistency and test-retest reliability. The relation with other measures was in the expected direction with stronger correlations for the theoretically-consistent variables, supporting convergent and divergent validity. CardioVascular Disease Acceptance and Action Questionnaire scores were associated with general psychological inflexibility, anxiety and depression and inversely correlated with psychological well-being. Moreover, the results showed that CardioVascular Disease Acceptance and Action Questionnaire scores are associated with two relevant risk factors for cardiac patients, namely low adherence to medication and being overweight. In sum, results suggest that the CardioVascular Disease Acceptance and Action Questionnaire is a reliable and valid measure of heart disease-specific psychological inflexibility with interesting clinical applications for secondary prevention care.